2021
DOI: 10.1016/j.celrep.2021.109609
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor controls exocytosis in chromaffin cells by increasing full-fusion events

Abstract: This is a repository copy of Glucagon-like peptide-1 receptor controls exocytosis in chromaffin cells by increasing full-fusion events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…In endocrine cells (e.g. pituitary lactotrophs, pancreatic β-cells and adrenal chromaffin cells) cAMP effects have been studied in the presence of Ca 2+ , leading to insights into regulation of Ca 2+ -evoked fusion pore behavior, electrical activity and peptide hormone release ( Calejo et al, 2013 ; 2014 ; Kucka et al, 2013 ; Guček et al, 2019 ; González-Santana et al, 2021 ). However, at the Drosophila NMJ, cAMP evokes release from DCVs in the absence of extracellular Ca 2+ and the presence of a Ca 2+ chelator without altering cytoplasmic [Ca 2+ ] ( Shakiryanova et al, 2011 ; Bulgari et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In endocrine cells (e.g. pituitary lactotrophs, pancreatic β-cells and adrenal chromaffin cells) cAMP effects have been studied in the presence of Ca 2+ , leading to insights into regulation of Ca 2+ -evoked fusion pore behavior, electrical activity and peptide hormone release ( Calejo et al, 2013 ; 2014 ; Kucka et al, 2013 ; Guček et al, 2019 ; González-Santana et al, 2021 ). However, at the Drosophila NMJ, cAMP evokes release from DCVs in the absence of extracellular Ca 2+ and the presence of a Ca 2+ chelator without altering cytoplasmic [Ca 2+ ] ( Shakiryanova et al, 2011 ; Bulgari et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The GLP-1R was recently shown to be present and functional also in adrenal chromaffin cells, where it modulates catecholamine (epinephrine and norepinephrine) secretion via the regulation of exocytosis ( Figure 3 ) [ 122 ]. Adrenal catecholamines are essential in the body’s response to stress [ 123 ] and, particularly, the hormone adrenaline (epinephrine) they uniquely (sympathetic neurons only release norepinephrine, the SNS neurotransmitter) secrete is vital for the generation of the classic “fight or flight” response of the body in situations of acute stress or danger [ 124 ].…”
Section: Sympathoadrenal Glp-1r-dependent Camp-mediated Signalingmentioning
confidence: 99%
“…Machado and colleagues reported that GLP-1R is expressed in bovine chromaffin cells and, interestingly enough, was found accumulating in the cytoplasm to a significant extent, which may suggest increased turnover of the receptor in response to the homeostatic status of the adrenal medulla (e.g., presence of stress signals, etc.) [ 122 ]. Moreover, the authors found that, although it is not a direct secretagogue of catecholamines, chromaffin cell GLP-1R enhances secretion in response to cholinergic stimulation of nicotinic cholinergic receptors (the physiological stimulus of adrenal catecholamine secretion), as well as the synthesis of catecholamines via tyrosine hydroxylase upregulation [ 122 ], the enzyme catalyzing the rate-limiting step in catecholamine biosynthesis [ 124 ] ( Figure 3 ).…”
Section: Sympathoadrenal Glp-1r-dependent Camp-mediated Signalingmentioning
confidence: 99%
See 2 more Smart Citations